2017
DOI: 10.5620/eht.e2017011
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of glyphosate in the germination of Pisum sativum and its effect on germinated seedlings

Abstract: The present study evaluated the effects of glyphosate on Pisum sativum germination as well as its effect on the physiology and biochemistry of germinated seedlings. Different physico-chemical biomarkers, viz., chlorophyll, root and shoot length, total protein and soluble sugar, along with sodium and potassium concentration, were investigated in germinated seedlings at different glyphosate concentrations. This study reports the influence of different concentrations of glyphosate on pea seeds and seedlings. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Glyphosate caused typical adverse alterations in the growth of wheat (Figure 1) expressed by obvious retardation of fresh biomass accumulation, and plant organs elongation, which is in accordance with earlier studies on different glyphosate-treated crops [4,9,12,14,28,43]. Glyphosate-suppressed plant growth is also a consequence of accumulation of ROS, which harm cellular biomembranes as is evidenced by the increased amount of MDA (Figure 2B).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Glyphosate caused typical adverse alterations in the growth of wheat (Figure 1) expressed by obvious retardation of fresh biomass accumulation, and plant organs elongation, which is in accordance with earlier studies on different glyphosate-treated crops [4,9,12,14,28,43]. Glyphosate-suppressed plant growth is also a consequence of accumulation of ROS, which harm cellular biomembranes as is evidenced by the increased amount of MDA (Figure 2B).…”
Section: Discussionsupporting
confidence: 89%
“…Glyphosate is a non-selective herbicide and it affects not only weeds but crop plants as well. A number of articles documented that it substantially altered germination and physiological responses of different crops such as pea [4,[6][7][8][9], faba bean and common bean [10], soybean [11], tomato [12,13], maize [14,15], sorghum [10], wheat [6,7], etc. That is why the modulation of the herbicide action by application of ecologically safe plant growth regulators, which are capable to reduce the negative effects of the herbicide on non-target plants, gives rise to interest of fundamental and applied outlook.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of radicles, unlike the hypocotyl, all genotypes were similarly affected, both in the treatment of 0.06% and 0.12%, reinforcing the hypothesis that glyphosate affects radicle development more than the hypocotyl, also seen in soybean by Tillmann and West (2004) and Heinz et al (2011), and in pea by Mondal et al (2017).…”
Section: Seedling Length Testsupporting
confidence: 71%
“…of cereal rye, hairy vetch, and winter wheat seeds soaked in the 0.7 g L -1 glyphosate solution was reduced by 48%, 74%, and 45%, respectively, compared to the nontreated control (Table 4). Mondal et al (2017) reported 55% and 40% reduction in field pea seed germination with exposure to 3 and 4 mg L −1 glyphosate solution, respectively. Segura et al (1978) reported 6% and 23% reduction in Italian ryegrass seed germination and 19% and 20% reduction in germination of red clover with glyphosate at 4 kg ha -1 applied directly to covered and uncovered seeds, respectively, compared to the nontreated control.…”
Section: Greenhouse Studymentioning
confidence: 99%